Inter-provincial transfer of carbon dioxide from construction industry in 30 provinces of China - ZHU Ying*; CUI Tianhao; TAN Jicong; LI Yexin; GUO Yong (能源环境保护)
Carbon dioxide (CO_2) emissions from construction industry in China account for approximately half of the country′s total CO_2 emissions. Given the frequent trade in the construction industry among regions, it is crucial to clarify the regional responsibilities for emission reduction in order to formulate reasonable emission reduction policies. To address the CO_2 emission situation and emission reduction responsibilities of China′s construction industry across different regions, a multi-regional input-output fuzzy network linear programming method (MFEP) is proposed. This method incorporates three modules, namely input-output analysis, fuzzy processing, eco-analysis, as well as five types of evaluation indexes. It enables the effective calculation of CO_2 transfer amounts and sheds light on the mutual utility relationship of transfers between regions, thereby elucidating the CO_2 reduction responsibilities of construction industry in China between regions. The results indicate that emission reduction targets should be lowered for provinces with rather high external contributions, such as Jiangsu (5.62) and Zhejiang (6.20), while emission reduction efforts should be increased for provinces with rather high external dependence, such as Tianjin (5.61) and Hebei (6.41). Additionally, adjusting the current energy structure, which is predominantly reliant on oil, and increasing the utilization of new energy sources like natural gas, can help offset the negative impacts of CO_2 transfer. This research outcome serves as a scientific reference and provides a strong basis for decision-makers in formulating emission reduction policies for the construction industry.